Comparison Between Efficacy of Norepinephrine and Phenylephrine Boluses for Prevention of Spinal Anesthesia-Induced Hypotension in Obstetrical Patients Undergoing Emergency Cesarean Section - Kamal, Rabia; Jamil, Muhammad Arsalan; Uzair, Shaista; Sultan, Syed Farjad (Biological and Clinical Sciences Research Journal, 2025)
Spinal anesthesia-induced hypotension (SAH) is a common complication during emergency cesarean sections, which can negatively affect both maternal and neonatal outcomes. This study aims to compare the efficacy of norepinephrine and phenylephrine boluses in preventing SAH in obstetric patients. Objective: To compare the efficacy of norepinephrine and phenylephrine boluses for preventing spinal anesthesia-induced hypotension (SAH) in obstetric patients undergoing emergency cesarean section. Methods: A double-blind randomized controlled trial was conducted at Dr. Ruth K.M. Pfau Civil Hospital Karachi, Dow University of Health Sciences, from 1st January 2025 to 31st March 2025. A total of 124 obstetric patients undergoing emergency cesarean section under spinal anesthesia were randomly assigned into two groups: norepinephrine (N) and phenylephrine (P). Each group consisted of 62 patients. The primary outcome was the incidence of hypotension following spinal anesthesia, while secondary outcomes included the need for additional vasopressor boluses, maternal and neonatal outcomes, and side effects. Statistical analysis was performed using Chi-square tests, with a p-value <0.05 considered statistically significant. Results: The overall incidence of hypotension was 58 (46.77%). The rate of spinal anesthesia-induced hypotension was significantly higher in the phenylephrine group compared to the norepinephrine group (56.45% vs. 37.1%; p=0.031). The proportion of infants with an Apgar score <7 at one minute was significantly higher in the phenylephrine group than in the norepinephrine group (33.9% vs. 6.5%; p=0.0005). Conclusion: A prophylactic bolus dose of norepinephrine demonstrated superior efficacy compared to phenylephrine for the prevention of spinal anesthesia-induced hypotension in parturients undergoing emergency cesarean section.